Model Bimbingan Konseling Islam untuk Mengatasi Burnout Pada Gen Z Melalui Integrasi Mindfulness Muraqabah - Vania Maovangi Day; Hajir Tajiri; Isep Zainal Arifin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the integration of mindfulness (a Western approach) with muraqabah (an Islamic approach) within Islamic Guidance and Counseling. This research is a literature-based study, with primary data sources derived from library materials. The findings indicate that the MMI model is also inspired by a framework integrating mindfulness with Islamic teachings, which promises greater therapeutic benefits for Muslim individuals, particularly in managing mental health issues such as chronic emotional exhaustion. Such integration has been proven to strengthen the therapeutic alliance and reduce therapy dropout rates among patients with religious backgrounds (Kamarulbahri et al., 2024b). Thus, this model functions not only as a technical tool but also as a spiritual means to guide Generation Z toward sustainable psychological balance in accordance with the principles of tasawuf (Islamic spirituality).